Magnitude and Implications of Poverty in Colombia - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Poverty is an important concept in the social sciences and its interpretation generally depends on the school of thought on which it is based. However, most of its scholars consider that poverty is the deprivation or deficiency of a condition or the obtaining of income in relation to a predetermined threshold.